2015
DOI: 10.15673/0453-8307.6/2015.56708
|View full text |Cite
|
Sign up to set email alerts
|

Порівняльні Результати Експериментальних Досліджень Різних Типів Плоских Сонячних Колекторів

Abstract: Full-scale traditional metal solar collectors and solar collector specimens fabricated from polymeric materials were investigated in the present study. A polymeric collector is 67.8% lighter than a traditional metal solar collector, and a metal solar collector with transparent plastic covering is 40.3% lighter than a traditional metal solar collector. Honeycomb multichannel plates made from polycarbonate were chosen to create a polymeric solar collector. A test rig for the natural circulation of the working fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Experimental investigation showed that the efficiency of the polymeric solar collector designed in the present study decreased 7-14% compared to traditional SCs [9,15,22].…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Experimental investigation showed that the efficiency of the polymeric solar collector designed in the present study decreased 7-14% compared to traditional SCs [9,15,22].…”
Section: Discussionmentioning
confidence: 95%
“…Analysis of polymeric materials used for solar collectors [22]. Most SCs are composed of the following elements: an absorber, a transparent cover, insulation, and a frame (Fig.…”
Section: Solar Collectors Designed For the Experimental Researchmentioning
confidence: 99%
See 3 more Smart Citations